Implementasi Metode House Of Risk Pada Evaluasi Keterlambatan Proyek Cable Tray Support di PT.SSS - Muhammad Dany Fauzi; Said Salim Dahda (Jurnal Serambi Engineering, 2023)
PT SSS is a company in the field of steel construction. In the Cable Tray Support project, delays occurred that affected the duration outside the contract. Projects have cost, quality, and time objectives that must be achieved. It requires good management of finance, equipment, materials, labor, and time. Therefore, project management is critical to the smoothness and success of the project. This research aims to identify delay problems through the House of Risk method, which analyzes risks, causative agents of delay, and mitigation strategies. There are 18 risks of delay with 21 causes identified, resulting in ten prioritized strategies, namely applying the material requirement planning method to find out more details of the lead time of each material, buying a lot at a lower price, looking for suppliers closer, overestimating the procurement index of certain types of materials, conducting strict and structured supervision to ensure the supply of appropriate goods from suppliers, evaluating the causes of delays and applying new methods to plan the arrival of materials, making a checklist of design drawings that have / have not been sent, making procedures for making and changing designs, updating the material list to facilitate material selection, improving coordination between consultants and field workers so that the design drawings can be said to be valid.